Strategi Pemasaran Syariah Usaha Kopra Di Kecamatan Rantau Rasau - Tutik Kurniawati; Anzu Elvia Zahara; Muhammad Subhan (JOURNAL SAINS STUDENT RESEARCH, 2023)
This thesis is entitled Sharia Marketing Stratrgy Copra In Rantau Rasau District and aims to know the sharia marketing. This research aims to find out how the sharia marketing strategy of copra business in pantau rasa district the research method that I use un this thesis is a qualitative research with a descriptive approach. The data used are primary and secondary data. Primary data were obtained from direct observation and from farmers giving information. The study collected information directly through interviews. Secondary data were obtained from the people of trimulya village, rantau rasau district. Based of the results of the research using price products, promotional, labor capital, and raw material. locarions in describing the results of the research used by analyzing internal and external factors carried out by providing an overview of the strangths, weaknesses, opportunities and threats possessed by farmers copra.